Pelatihan dan Pendampingan Usaha Produksi dan pemasaran berbasis Web Limbah bawang merah menjadi pupuk organik kompos dan pupuk organik cair pada UMKM - Abdulah, Budiman; Ruseno , Ndaru; Suryaningsih, Fina; ,, Nurdiana (Al-Khidmah Jurnal Pengabdian Masyarakat, 2024)
This community service with an entrepreneurship-based empowerment scheme aims to improve understanding of production machines, low productivity, financial reporting and digital marketing management for MSMEs in Kramat Jati, East Jakarta. The problems faced by partners in this program are related to the manual process of chopping onion waste, weak production management, finance and marketing which have not been managed well. This method of implementing entrepreneurship-based empowerment uses the Participatory Action Research (PAR) method, which is carried out starting from the socialization stage at the beginning of community service activities, in the form of providing information to partners/community about community service activities to be carried out, activity objectives, stages of activity implementation, and activity implementation schedules based on agreement between the proposing team and partners, the next stage is training and mentoring and evaluation of activities. The results of the activity showed an increase in partners' knowledge regarding production management, finance and digital marketing as well as understanding the use of machines in production before and after the training.